Analisis Nilai Tukar Terhadap Cadangan Devisa Indonesia - Jasa Ginting (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The position of a country's foreign exchange reserves is usually declared safe if it meets the import needs for a period of at least three months. If the foreign exchange reserves that are owned are not sufficient for three months of imports, then it is considered vulnerable. This study aims to determine the effect of the exchange rate on Indonesia's foreign exchange reserves. The data in this study are monthly time series data from 2013-2019 sourced from Bank Indonesia. The data obtained were then analyzed by simple linear regression using software eview 9.0. The results showed that the exchange rate (exchange rate) had a significant effect on Indonesia's foreign exchange reserves.